Cognitive Aspects of Criminal Justice Policy - VILKS, Andrejs; KIPĀNE, Aldona (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018DO - 10.14505//jarle.v9.5(35).35, 2018)
The relevance of this article is that the criminal justice policy has not been given enough attention and is rarely mentioned in legal literature. The purpose of this article is to analyze the cognitive aspects of criminal justice policy. The article provides an insight into criminal justice policy in the area of crime prevention and combating. In the article the analysis of legal and criminal policy concepts are described, analyzing their nature. Criminal law policy is viewed, considering the requirements of international legal acts as well. Criminal law policy is also outlined as one of the instruments for solution of social problems. As to its nature, it is the activity of a special state and municipal institution type directed at strengthening of national legal system. This research will be readable for lawyers, judges and other people who is interesting in criminal justice system and its aspects.